A Pilot Study on the Influence of Facial Expression on Measurements in Three-Dimensional Digital Surfaces of the Face in Infants with Cleft Lip and Palate. (January 2016) - Hermann, N.V.; Darvann, T.A.; Larsen, P.; Lindholm, P.; Andersen, M.; Kreiborg, S.
Objective: Three-dimensional surface imaging is an increasingly popular modality for face measurements in infants with cleft lip and palate. Infants are noncompliant toward producing specific facial expressions, and selecting the appropriate moment of acquisition is challenging. The objective was to estimate amount and spatial distribution of deformation of the face due to facial expression in infants with cleft lip and palate and provide recommendations for an improved acquisition protocol, including a method of quality control in terms of obtaining images with true neutral expression. Material and Methods: Three-dimensional surface images of ten 4-month-old infants with unrepaired cleft lip and palate were obtained using a 3dMDface stereophotogrammetric system. For each subject, five surface images judged as representing a neutral expression were obtained during the same photo session. Mean and maximum deformations were calculated. A formalized review was performed, allowing the image exhibiting the "best" neutral expression to be selected, thus decreasing errors due to residual facial expression. Results: Deformation due to facial expression generally increased from forehead to chin. The amount of deformation in three selected regions were determined: nose (mean, 1 mm; maximum = 3 mm); cleft region (mean, 2 mm; maximum = 5 mm); chin region (mean, 5 mm; maximum = 12 mm). Analysis indicated that introduction of a formalized review of images could reduce these errors by a factor of 2. Conclusions: The continuous change of facial expression in infants represents a substantial source of error; however, this may be reduced by incorporating a formalized review into the acquisition protocol.